Unique case series of tubercular neck abscess at a primary care centre in the Eastern part of Nepal. - Pyakurel, Pradeep Kumar (Journal of Gandaki Medical College-Nepal, 2021)
Cervical tubercular lymphadenopathy(CTL) is a common extra-Pulmonary manifestation of tuberculosis. CTL can masquerade many other diseases. A high index of suspicion must be maintained in any cases presenting with neck swelling especially in TB endemic region like Nepal. Here we present a varied presentation of CTL at a primary care level community hospital.